Development and Effectiveness of a Comprehensive Program for Evaluating the Performance of the Educational System on the Result of Evaluation and Educational Accreditation of Shahid Beheshti Hospital in Babol - somayeh Oladi (Babol University of Medical Sciences, 2020)
ABSTRACT BACKGROUND AND OBJECTIVE: In order to evaluate the performance of teaching hospitals, the patterns of accreditation system as one of the most important packages of transformation and innovation plan in medical education, considered by the Ministry of Health. One of the serious challenges of the educational accreditation program is the use of a same standard set to evaluate the educational programs of the educational-medical centers. The aim of this study was to determine the effect of a comprehensive program for evaluating performance of educational system as results of evaluation and educational accreditation of Dr. Shahid Beheshti Hospital in Babol. METHODS: This quasi –experimental study was performed in Shahid Beheshti hospital in Babol in 1397. A comprehensive program for evaluating performance of educational system was developed by accreditation team through the method of brainstorming and reviewing texts. The program was piloted for six months. The evaluation results of the years of 1397 and 1398 were extracted from the country's accreditation system and compared with our data. FINDINGS: The score obtained before and after the intervention was 242 points and 445 points, respectively. The results showed that the most effect of the comprehensive program in the domain of monitoring and evaluating the performance of the educational system (86.1%) and the least effect was seen in the field of clinical research (44.48%). CONCLUSION: Due to the significant increase in points obtained from the evaluation in 1397 compared to the past and improving the educational status of the center, as well as the high satisfaction of the executive management team, it is suggested that a comprehensive program to evaluate the performance of the educational system as a model for the principled and effective implementation of accreditation used in other centers.